Influence of precipitation and plant age on the production and chemical composition of the bufell grass - Neto, José Dantas; Silva, Francisco de Assis Santos e; Furtado, Dermeval Araújo; Matos, José de Arimatéia de (Pesquisa Agropecuaria Brasileira, 2000)
The experiment was conducted at the micro region of Cariris Velhos, Paraíba State, Brazil, and its objective was to observe the influence of precipitation and age of the plant at the first cut on the production of dry matter and chemical composition of the buffel grass. This precipitation was simulated by water application through a gun sprinkler system irrigation. The experimental design used was a randomized block with six replications, and the treatments consisted of combining five water depths and six ages at the first cut. The water application increased the dry matter production in all plant ages at the first cut; the estimated maximum yield of 5,191 kg ha-1 occurred with a water depth of 334 mm, and the cut was done 80 days after germination. The amount of applied water did not influence the crude protein content; however, it decreased linearly with the age of the plant. The crude fiber content increased with the amount of water applied. The age of the plant at the first cut did not influence the percentage of crude fiber.